2019
DOI: 10.1186/s12913-019-4475-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of client satisfaction with family planning services in public health facilities of Jigjiga town, Eastern Ethiopia

Abstract: Background Client satisfaction is the best indicator of quality service provision and has been found to correlate with continuity of care perceived by the client. The measurement of client satisfaction helps in understanding willingness and decisions to return for future services. Thus, this study aimed at assessing the level and factors associated with client satisfaction of FP services among family planning users. Methods An institutional based cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
4
6
2
4
Order By: Relevance
“…The odds of reporting satisfaction is higher among clients who get a clear description of the side-effects of the method as compared to their counterparts. This evidence is consistent with study findings from Jigijiga 21 and a countrywide study in Ethiopia. 11 The finding implies the counseling on side effects could improve satisfaction and indirectly improve service quality.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The odds of reporting satisfaction is higher among clients who get a clear description of the side-effects of the method as compared to their counterparts. This evidence is consistent with study findings from Jigijiga 21 and a countrywide study in Ethiopia. 11 The finding implies the counseling on side effects could improve satisfaction and indirectly improve service quality.…”
Section: Discussionsupporting
confidence: 92%
“…The magnitude of client satisfaction with family planning services was found to be 46%. This finding was consistent with studies conducted in Jigijiga (41.7%), 21 Wonji (45%) 13 eastern Ethiopia and Congo (42%). 14 This finding is lower than studies conducted in Bahirdar (66.1%), 22 Hossana (75.3%), 10 west Shawa (62.6%), 7 countrywide Ethiopia (58.5), 11 Tanzania (91%), 12 Mozambique (86%), 9 Bangladesh (75), 23 and Mexico (80%).…”
Section: Discussionsupporting
confidence: 92%
“…Compared with these existing studies, our study focused on western rural residents and had a good sample representation to some extent based on a large sample, so the findings in our study could better reflect rural resident experience with BPHSs in Western China. Internationally, Gebreyesus found that 41.7% of rural clients were satisfied with family planning services in public health facilities in a town of Eastern Ethiopia [49], Gitobu et al reported a satisfaction rate of 54.5% of mothers with free maternal healthcare services provided by public health facilities in Kenya [50]. From the overall satisfaction perspective, we could conclude that some positive effects had been achieved by the rural BPHSs' delivery system in China however, there is still much to be improved for rural patients' overall satisfaction rate or satisfaction score.…”
Section: Discussionmentioning
confidence: 99%
“…The Quick Investigation of Quality (QIQ) is a facility-based survey intended to provide a comprehensive picture of family planning services (FPS) in low- and middle-income countries, developed as the latest tool for FPS evaluation for ‘MEASURE Evaluation’ in 2013 by USAID [ 14 – 17 ]. It uses three different measurement tools: facility audits, structured observations and exit interviews with clients [ 14 ].…”
Section: Methodsmentioning
confidence: 99%